Comparison Effect of Direct Trocar and Veress Needle Entry Techniques on Gut Functions after Laparoscopic Procedures: Randomized Clinical Trial - Taylan Şenol; Mesut Polat; Enis Özkaya; İlhan Şanverdi; Birsen Konukçu; Ateş Karateke (Medical Network, 2016)
OBJECTIVE: The aim of this study was to compare the effect of two different laparoscopic entry methods on postoperative gastrointestinal functions. STUDY DESIGN: A total of 108 women who underwent gynecological operation via laparoscopic approach with different indications were randomly assigned to 2 groups: In Group 1 pneumoperiteneum was achieved by direct trocar entry (n=72), while in group 2, Veress needle was used. RESULTS: Correlation analyses showed a significant association between the technique for abdominal entry and postoperative hemoglobin and hematocrit concentrations, time to maximal intraabdominal pressure and the body mass index. Comparison of groups with different laparoscopic entry techniques showed a significant difference between groups in terms of postoperative hemoglobin and hematocrit concentrations, time to obtain maximal intraabdominal pressure and time to first flatulence (p < 0.05, Table 2). No intra or postoperative complications was observed. CONCLUSION: Direct or Veress needle entry methods were both safe to create pneumoperitoneum with similar postoperative gastrointestinal functions except for earlier first flatulence in Veress needle group while direct trocar entry was found to be associated with favorable postoperative blood count and shorter duration to obtain enough intraperitoneal pressure.